Transformasi Manajemen Fasilitas Pendidikan Pada Era Disrupsi Teknologi - Galih Abdi Nugraha; Baidi Baidi; Syamsul Bakri (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine the transformation of educational facility management in the era of technological disruption, where the place of this research was carried out at Duta Bangsa University, Surakarta. The methodology in this study uses a qualitative approach. Data collection techniques in this study are by observation, interviews and documentation. The method used to check the validity of the data is the triangulation method, namely by utilizing various methods as a consideration. The data analysis technique in this study is data that has been obtained by descriptive (non-statistical) method. Activities in data analysis, namely data reduction (data reduction), data display (data presentation), and verification (drawing conclusions). The results show that the transformation of educational facility management in the era of technological disruption that has been carried out by Duta Bangsa University Surakarta continues to be carried out starting from educational services that are directed towards technology-based both physical and non-physical in supporting universities, as well as in the implementation of all technology-based learning as a demands for technological developments that are happening more rapidly (disruption) in order to create a superior campus in the era of technological disruption.